Buddhistische Verhältnisbestimmungen zu anderen Religionen - Jäger, Stefan S. (Evangelische Theologie, 2024)
This article explores some basic Buddhist attitudes towards other religions as found in the history of the spread of Buddhism in Asia and, since the 19th century, in the Americas and Europe. In the encounter with other religious traditions, Buddhist formations prove to be highly adaptable and integrative in terms of specific elements, while holding on to fundamental insights. Particular emphasis is placed on Buddhist meta-communicative concepts and terminology. Since Buddhism is basically a non-theistic religion, its encounter with theistic religions can be characterized as asymmetrical.